PENGARUH PROGRAM CUSTOMER RELATIONSHIP MANAGEMENT TERHADAP LOYALITAS PELANGGAN CAFÃ HERBAL JAMU GODHOG - , AYU PUSPITASARI; , Novita Erma Kristanti, STP. M.P. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Currently public awareness of the importance of healthy living is increasing. People's lifestyles shifted to the back to nature. Therefore traditional medicine more demand so that its use increases. But this is contrary to what happens in the CafÃ© Herbal âJamu Godhogâ. Where the observations made, it is known that the number of sales in the CafÃ© Herbal âJamu Godhogâ instability. Sales unstable means that customer loyalty CafÃ© Herbal âJamu Godhogâ still low. To retain customers CafÃ© Herbal âJamu Godhogâ implementing one of marketing strategy is Customer Relationship Management. The purpose of this study was to determine the effect of the implementation of CRM on customer loyalty programs CafÃ© Herbal âJamu Godhogâ and formulate proposals for appropriate CRM programs CafÃ© Herbal âJamu Godhogâ. In this study, the method used is multiple linear regression. Multiple linear regression was used to analyze the influence of these variables (customer service, loyalty programs, and community building) on customer loyalty. Regressions were analyzed using SPSS 16.0 software . The results of this study, namely, CRM variables have a significant effect on customer loyalty at 79.1% with a multiple linear regression equation Y= 1.853 + 0.324X1 + 0.424X2 + 0.129X3, with X1 is customer service variable, X2 is loyalty program and X3 is community building. CRM program proposals submitted to customers are very loyal to update SOP, held membercard program, and create a website and facebook. Meanwhile, to attract new customers is to improve the quality of products and services and conduct rebate programs according to age.